Identification of a novel ATP-binding cassette transporter involved in long-chain fatty acid import and its role in triacylglycerol accumulation in Rhodococcus jostii RHA1 - Villalba, María S. (2014)
Members of Rhodococcus genus are specialists in the biosynthesis and accumulation of triacylglycerols (TAG). Since no transport protein related with TAG metabolism has been characterized until now in these bacteria, we used the available genomic information of Rhodococcus jostii RHA1 to perform a broad survey of genes coding for putative lipid transporter proteins in this oleaginous microorganism. Among the seven genes encoding for putative lipid transporters, ro05645 (now called ltp1: lipid transporter protein) coding for an ABC protein was found clustered with others genes encoding for enzymes catalyzing the three putative acylation reactions of the Kennedy pathway for TAG synthesis. Overexpression of ltp1 gene in the RHA1 strain led to an increase of approximately six- and three-folds in biomass and TAG production; respectively, when cells were cultivated on palmitic acid and oleic acid. Moreover, overexpression of ltp1 also promoted a significant increase in the uptake of a fluorescently labeled long-chain fatty acid in comparison with the wild type strain RHA1, and its further incorporation into the TAG fraction. Gluconate-grown cells showed increasing amounts of intracellular free fatty acids, but not of TAG, after overexpressing ltp1 gene. Thus, for the first time to our knowledge, a transporter functionally related to TAG metabolism was identified in oleaginous rhodococci. Our results suggest that Ltp1 is an importer of long chain fatty acids, which plays a functional role in lipid homeostasis of R. jostii RHA1.